FAIRNESS IN THE DISTRIBUTION OF ROYALTIES FOR PERFORMERS AND RECORD PRODUCERS AS RELATED RIGHTS HOLDERS - Andry Dwiarnanto; Faisal Santiago (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2026)
Related rights, integral to intellectual property safeguards, confer economic entitlements upon contributors to phonogram performance and production. Royalty allocation to beneficiaries proceeds principally via Collective Management Institutions (LMK) and the National Collective Management Institution (LMKN), per Law Number 28 of 2014 on Copyright and Government Regulation Number 56 of 2021 on Song and/or Music Copyright Royalty Administration. Employing normative juridical methodology with statutory and conceptual emphases, this study reveals that despite normative royalty frameworks, practical hurdles persist: opaque LMK oversight, deficient work utilization tracking, and user noncompliance with payment duties. Moreover, equitable royalty apportionment for performers and producers remains suboptimal. Regulatory fortification, LMK transparency elevation, and digital technology adoption are imperative for equitable, efficacious distribution benefiting related rights stakeholders.